Chromatin structure and context-dependent sequence features control prime editing efficiency - Kim, Somang; Yuan, Jimmy B.; Woods, Wendy S.; Newton, Destry A.; Perez-Pinera, Pablo; Song, Jun S. (Frontiers in Genetics, 2023)
Prime editor (PE) is a highly versatile CRISPR-Cas9 genome editing technique. The current constructs, however, have variable efficiency and may require laborious experimental optimization. This study presents statistical models for learning the salient epigenomic and sequence features of target sites modulating the editing efficiency and provides guidelines for designing optimal PEs. We found that both regional constitutive heterochromatin and local nucleosome occlusion of target sites impede editing, while position-specific G/C nucleotides in the primer binding site (PBS) and reverse